Relationship between Lead Exposure and Genotoxic Effect in Paint Industry Workers - Rahman, Intan Nur’azizah; Oginawati, Katharina; Ismawati, Yuyun; Buftheim, Sonia; Nugrahaningsih, Dwi Aris Agung (Devotion : Journal of Research and Community Service, 2023)
Lead-based paint is a main source of lead exposure to paint industry workers and causes an imbalance of Reactive Oxygen Species (ROS) and antioxidants, causing a genotoxic effect. Pb in the blood (PbB) level and DNA damage are frequently used as exposure and effect biomarker of lead. The purpose of this study to determine the relationship between PbB level and DNA damage due to occupational lead exposure in paint industry workers. The research design uses a cross-sectional epidemiological study involving 52 workers from three paint manufacturers in Indonesia. Blood samples were taken for PbB analysis using ICP-MS, while DNA damage was analyzed using the Comet Assay method. The PbB average obtained was 4.36±1.60 µg.dL-1, where 17 workers (32.69%) exceeded the safe limit value of PbB (5 µg.dL-1). Meanwhile, the influential factors of PbB are the working period and alcohol consumption (p=0.029). The level of DNA damage was represented as Tail DNA (%), and the average was 9.62±0.19 %. All respondents in this study were categorized as under low damage (Class 2). There was no significant relationship between PbB and Tail DNA (%) and has a negative correlation (p=0.878; r=-0.022). The study concludes that there was no difference in Tail DNA (%) between PbB ≥ 5 µg.dL-1 and PbB < 5 µg.dL-1 (p=0.876). It means that lead exposure in this finding has not reached a level that can significantly cause DNA damage. However, it is necessary to monitor PbB levels in workers to minimize genotoxic or other effects.